The competitiveness landscape in Central and Eastern Europe - Myszkowska, Magdalena (Economics of the 21st Century, 2015)
The aim of the paper is to present the competitiveness landscape of 10 Central and Eastern European countries: Bulgaria, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, the Slovak Republic and Slovenia (CEE). The analysis covers various interrelated competitiveness factors, including enterprise environment, education, labour market and employment, innovation, technological progress thus allowing one to identify various aspects of competitiveness and provide insights into what drives the productivity and prosperity in these countries. The performance level of each of the CEE country is compared with others from that group; additionally a comparison is made with other European regions, some advanced economies and large emerging economies. The paper analyses and measures the competitiveness of the CEE, the extent to which progress is made in terms of achieving the competitiveness goals, and points out the key reforms and investments that implementation CEE countries should consider in order to tackle the existing challenges and close the competitiveness gap between other EU countries as well as other more advanced. This could serve as a starting point for defining a widely supported competitiveness agenda aiming at a long-term and stable economic and social progress throughout the CEE region
Ekonomia XXI Wieku = Economics of the 21st Century, 2015, Nr 4 (8), s. 9-19
Keywords: Central and Eastern Europe; competitiveness; productivity; Europa Środkowo-Wschodnia; konkurencyjność; produktywność